Strategi inovasi layanan digital bank syariah indonesia untuk meningkatkan kepuasan nasabah - Rahma, Anida Salsabila (Maliki Interdisciplinary Journal, 2025)
The rapid advancement of digital technology requires financial institutions, including Bank Syariah Indonesia (BSI), to innovate in improving service quality. This study aims to analyze the digital service innovation strategies implemented by BSI to enhance customer satisfaction in the digital era. The method used is qualitative descriptive with a literature study approach from various academic sources. The results show that innovations such as the development of the BSI Mobile application, enhanced digital transaction security systems, and the improvement of Sharia-based service features strengthen customer trust and convenience. In addition, responsive and educational digital communication strategies play an important role in building a positive image of the bank among users. These findings emphasize that the success of digital innovation management strategies depends on the synergy between technology, Sharia values, and customer satisfaction orientation hus, integrating digital innovation based on Sharia principles becomes a key factor in strengthening the competitiveness and sustainability of Islamic banking services.